An Investigation of Pre-Service English Teachers’ Awareness of English as a Lingua Franca and World Englishes - Öztürk, Samed Yasin (Mus Alparslan Üniversitesi, 2021)
English as a Lingua Franca (ELF) and World Englishes (WE) have appeared as a reaction to
Keywords: Other Fields of Education; Alan Egitimleri